Examining Indonesian EFL Teacher Educators’ Views on Utilising L1 in L2 Classrooms - Abid Abid (Lingua Cultura, 2020)
The research observed the role of the first language (L1) use in the second language (L2) classrooms in various Englishlanguage teaching (ELT) contexts. Among the many roles that L1 use played in L2 classrooms, which had been recognized, some drawbacks interfered due to unbalanced uses of both L1 and L2. To complement insightful findings presented in the existing literature on this L1 use topic, the research aims to explore L1 uses in English as a Foreign Language (EFL) L2 classrooms in a teacher training program in Indonesia. Applying a qualitative research approach, the research collected data from three English as a foreign language (EFL) teacher educators teaching an English speaking subject in an Indonesian university using a semi-structured interview protocol and a classroom observation fieldnote. Results show that all the participants share the same views on L1 in their L2 classrooms that its use is tolerated and mainly related to cognitive and pedagogical aspects. The research suggests that formal training seeking to arouse awareness on the role that L1 can play in L2 classroom is of necessity in the context of the EFL teacher training program in order to foster learners’ optimal L2 output.